Consequences of producing DNA gyrase from a synthetic gyrBA operon in Salmonella enterica serovar Typhimurium - Dorman, Charles (My University, 2021)
DNA gyrase is an essential type II topoisomerase that is composed of two subunits, GyrA and GyrB and has an A 2 B 2 structure. Although both subunits are required in equal proportions to form DNA gyrase, the gyrA and gyrB genes that encode them in Salmonella (and in many other bacteria) are at widely separated locations on the chromosome, are under separate transcriptional control and are present in different copy numbers in rapidly growing bacteria ( gyrA is near the terminus of chromosome replication while gyrB is near the origin). We generated a synthetic gyrBA operon at the oriC -proximal location of gyrB to test the significance of the gyrase gene position for Salmonella physiology. Producing gyrase from an operon did not alter growth kinetics, cell morphology, competitive fitness index, or sensitivity to some gyrase-inhibiting antibiotics. However, the operon strain had altered DNA supercoiling set points, its SPI-2 virulence genes were expressed at a reduced level and its survival was reduced in macrophage. The gyrB gene could not be deleted from its oriC -proximal location, even in a gyrB merodiploid strain. We discuss the physiological significance of the different gyrA and gyrB gene arrangements found naturally in Salmonella and other bacteria.
PUBLISHED
Published online 4.02.2021
Keywords: Salmonella entericaserovar Typhimurium; DNA gyrase; gyrA; gyrB; DNA supercoiling; SPI-1; SPI-2